Situational effects of mathematics anxiety in pre-service teacher education - Cooke, Audrey; Cavanagh, Rob; Hurst, Chris; Sparrow, Len (Australian Association for Research in Education, 2011)
The new National Program Standards for Accreditation of Initial Teacher Education states that 'applicants' levels of personal literacy and numeracy should be broadly equivalent to those of the top 30 per cent of the population' (Australian Institute for Teaching and School Leadership [AITSL], 2011, p. 13) or, if pre-service teachers enrolled in the degree have not met this equivalence, institutions 'must establish satisfactory additional arrangements to ensure that all students are supported to achieve the required standard before graduation' (AITSL, 2011, p. 13). This places an emphasis on the numeracy and mathematical skills of the pre-service teachers completing the Early Childhood and Primary bachelor degrees. However, little consideration is given in their teaching qualification preparation to the anxiety these pre-service teachers may have towards mathematics. Pre-service teachers with mathematics anxiety may avoid mathematics (Isiksal, Curran, Koc, & Askum, 2009), may have lower teacher efficacy in mathematics (Gresham, 2008), may experience a negative impact on their teaching behaviours (Swars, Daane, & Giesen, 2007), may pass on their anxiety to their students (Malinsky, Ross, Pannells, & McJunkin, 2006), and may negatively influence the mathematics achievement of their students (Beilock, Gunderson, Ramirez, & Levine, 2009).The aim of this project was to determine whether a modified version of the self- report instrument developed by Cavanagh and Sparrow (2010a; 2010b) could measure mathematics anxiety in pre-service teachers. Specifically the project investigated different situations - in a university class, when completing a formal mathematics test, and when teaching. Data from 169 pre-service teachers were analysed using the Rasch Rating Scale model (Andrich, 1978a, 1978b &1978c). The results showed that data from the instrument complied with the requirements of the Rasch model. The results also enabled comparisons to be made of student scores in the three situations. The paper concludes by discussing the potential benefits of using the instrument in a diagnostic and formative way to inform pre-service teachers of the possible level of mathematics anxiety they might experience.